An equation associated with the distance between probability distributions - Kannappan, PL.; Sahoo, P.K.; Chung, J.K. (Annales Mathematicae Silesianae, 1994)
In this paper, we solve the functional equation f1(pr,qs) + f2(ps,qr) = g(p,q)h(r,s) (p,q,r,s∈]0,1]) where f1,f2,g,h are complex-valued functions defined on ]0,1]. This functional equation is a generalization of a functional equation which was instrumental in the characterization of symmetric divergence of degree α in [3]. This equation arises in the characterization of symmetric weighted divergence of degree α and symmetric inset divergence of degree α.